Analisis Rhodamin B pada Lip Tint Menggunakan Metode Kromatografi Cair Kinerja Tinggi (KCKT) - Puspitasari, Lia; Azizah, Kholipia; Thalib, Amlius (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Rhodamine B is a dangerous colorant and is prohibited for use in various cosmetic products. The aim of this study was to analyze Rhodamine B in lip tint cosmetics, using the High Performance Liquid Chromatography (HPLC) system. Quantitative determination of Rhodamine B was carried out on 8 samples consisting of 4 BPOM registered samples and 4 non BPOM registered samples. The samples were taken at the Cakung traditional market with a randomized sampling method. The quantitative analysis of Rhodamine B by HPLC was carried out with a C18 stationary phase and a mobile phase of a mixture of acetonitrile and diammonium hydrogen phosphate (80:20); the sample injection volume was 20 µl and the eluent flow rate was 0.71 mL/minute. The results showed that Rhodamine B was not detected in the 8 lip tint samples tested.